EFFECTS OF IMMUNIZING PREGNANT EWES AND DOES ON THE HUMORAL IMMUNE RESPONSE OF SECRETED COLOSTRUM - H. A. Burezq; M. A. Razzaque (Journal of Animal and Plant Sciences, 2017)
To produce hyperimmune colostrum of ewes and does by vaccinating them during their pregnancy and to examine the performance of their lambs/kids receiving the colostrum from the dams. Animals were divided as those under control (T-1) without vaccination and those under 3 treatments of vaccinated flocks (T2-T4). The vaccines used in this study were; Clostridia sp (CZ Veterinaria S.A Spain), Pasteurella sp. (CZ Veterinaria S.A Spain), and Sheeppox (Biosciences, Jordan). Study variables were concentration of immunoglobulins (Igs) in both serum and colostrum of ewes and does as well as quantifying the IgG classes in the serum of offspring of both species. Body condition scores (BCS) and live weight changes of both species were also examined. Effects of vaccination of pregnant ewes and does were clearly indicated by doubling of serum Igs in vaccinated dams compared to control. Likewise, the colostrum of the dams of both species considered as hyperimmune contained (20.89±1.22 mg/ml) in T-1 (control without vaccination), and with vaccination T-2 (Clostridia sp., 43.45±0.06 mg/ml), T-3 (Pasteurella sp., 46.22±0.150 mg/ml) and T-4 (Sheep pox 47.13±0.11mg/ml); the corresponding values for does were T-1 19.25±0.22 mg/ml, T-2 39.25±0.5 mg/ml, T-3 40.5±1.3 mg/ml, and T-4 45.2± 2.3 mg/ml, respectively. Hyperimmune colostrum intake by the offspring had a significant positive impacts on the concentration of total of immunoglobulins-gamma (IgG) and Ig classes (IgG, IgM, IgA) in the blood sera. Most important positive effects were in increasing IgG from control (22.0±2.0 mg/ml) to T-2 (33.0±0.32 mg/ml), T-3 (35.0±1.20 mg/ml), and T-4 (32.0±0.87 mg/ml), respectively in lambs; the corresponding values for kids for T-1, T-2, T-3, were T-1 (19.12±0.91 mg/ml), T-2 (36.0±0.39 mg/ml), T-3 (33.0±0.56) and T-4 (35.0±0.21 mg/ml), respectively. Our studies concentrated initially in challenging the ewes/does with any individual vaccines of Clostridia sp., Pasteurella sp., and Sheep pox. Morbidity and mortality rates during the early 7 days of age of offspring were almost none in vaccinated flocks compared to those without vaccination. The benefits of pregnant small ruminant vaccination were clearly demonstrated in our studies. However, the effects of combined vaccine use for pregnant dams are yet to be investigated (underway) on offspring until weaning.
Keywords: Hyperimmune colostrum; immunoglobulin; vaccination; mortality; lambs; kids